legitimidad, complicidad y conspiración: la emergencia de una nueva forma económica en los márgenes del estado en Colombia - María Clemencia Ramírez (Antípoda: Revista de Antropología y Arqueología, 2014)
Between 2003 and 2008, DMG, a trading company with some of the characteristics of a classic pyramid scheme, challenged Colombia's core financial order, indicating the emergence of an alternative economic structure in a marginal part of the country. DMG's model was an amalgam of legal and illegal economic activities in a region dominated by the illicit drug economy. This article argues that the inhabitants of Putumayo Department, tired of demanding full inclusion in the nation-state and moved by feelings of abandonment and resentment at drug policies that criminalized them, legitimized and even identified with the activities of DMG, which offered them access to levels of wellbeing denied them by the state.